1989
DOI: 10.1007/978-3-662-05671-4
|View full text |Cite
|
Sign up to set email alerts
|

U Uranium

Abstract: This work is subject to copyright. ALL rights are reserved, whether the whoLe or part of the materiaL is concerned, specifically those of translation, reprinting, reuse of illustrations, broadcasting, reproduction by photocopying machine or similar means, and storage in data banks. Under §54 of the German Copyright Law where copies are made for other than private use, a fee is payabLe to "VerwertungsgeseLLschafl Wort", Munich. © by Springer-VerLag Berlin HeideLberg 1989 Originally published by Springer-Verl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
(18 reference statements)
0
3
0
1
Order By: Relevance
“…Ganesan et al 30 also found the post-exposure weight losses for the annealed samples, under static Na, were less than those reported in dynamic Na environments. 31 The weight loss in the annealed samples was also seen to be less than the 20% found in cold worked 316 stainless steel samples. 32,33 As with Suzuki et al 28 the σ-phase was found to nucleate near the exposed surfaces.…”
Section: Summary Task D: Reaction With Molten Metalsmentioning
confidence: 82%
“…Ganesan et al 30 also found the post-exposure weight losses for the annealed samples, under static Na, were less than those reported in dynamic Na environments. 31 The weight loss in the annealed samples was also seen to be less than the 20% found in cold worked 316 stainless steel samples. 32,33 As with Suzuki et al 28 the σ-phase was found to nucleate near the exposed surfaces.…”
Section: Summary Task D: Reaction With Molten Metalsmentioning
confidence: 82%
“…In the United States, in the late 1960s, a large-scale development program on vanadium alloys was undertaken by the Atomic Energy Division at Westinghouse. Wide-ranging cooperative research projects in the Federal Republic of Germany in 1964 -1971 are reported in [31], [50], [51]. A comprehensive review of these developments can be found in [7].…”
Section: Usesmentioning
confidence: 99%
“…The behavior of vanadium and its alloys in contact with lithium and sodium is described in [11], [51]. The effect of irradiation by neutrons on the strength properties of vanadium and its alloys is described in [52].…”
Section: Usesmentioning
confidence: 99%
“…Die Tatsache, dal3 Kohlenstoff mit Natrium nur die instabile Verbindung Nap22 bildet, ist der Grund fur eine hohe chemische Aktivitat des gelosten Kohlenstoffs, der sich wie das geloste Element verhalt [2]. Kohlenstoffgehalte in Natriumkreislaufen werden durch dieTemperatur der Kaltfalle beeinflufit, sie sind jedoch vie1 hoher, als der Sattigungskonzentration bei der Kaltfallentemperatur entspricht [3]. Stahle (3)…”
Section: Kohlenstoff Im System Natrium -Stahlunclassified